AB0680 Analysis the causes and countermeasures of ignoring swallowing dysfunction in patients with polymyositis and dermatomyositis. (15th June 2017) - Wen, Y; MinLi, Q; Yan, L
Abstract : Background: The patients with Polymyositis and Dermatomyositis always ignored swallowing dysfunction and most of them eventually had no enough knowledge of this. For this situation, to find out the reasons and take appropriate measures was necessary. Objectives: To analyze the causes of ignoring swallowing dysfunction in patients with Polymyositis and Dermatomyositis and to explore the corresponding preventive measures. Methods: The clinical data of 47 patients with Polymyositis and Dermatomyositis in hospital from September 2012 to December 2013 was analyzed retrospectively. The swallowing function was evaluated by the water swallow test, and the patients' knowledge of swallowing dysfunction was surveyed. Results: Only 2 patients complained of choking during swallowing, with ignorance rate of 95.74%. Positive rate was 40.43% in water swallow test, of which grade II dysphagia proposition was 58%, III grade was 32%, IV grade was 10%. 100% of patients believed that sternal obstruction or dysphagia as swallowing dysfunction. 89.36% of patients didn't think drinking water with bucking as swallowing dysfunction. Conclusions: The symptoms of limb weakness in patients with Polymyositis and Dermatomyositis may obscure the presence of dysphagia. In addition, the patients do not have enough knowledge about dysphagia that to neglect the swallowing dysfunction. To improve detection rate of swallowing dysfunction in patients with Polymyositis and Dermatomyositis, earching detailed history by listing dysphagia performance and providing water swallow test is necessary. References: Comparison between swallowing-related and limb muscle involvement in dermatomyositispatients. Kim SJ, Han TR, Jeong SJ, Beom JW. Scand J Rheumatol. 2010 Aug;39(4):336–40. Disclosure of Interest: None declared